2017
DOI: 10.1021/acs.iecr.7b00328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micellization on Growth Kinetics of Methane Hydrate

Abstract: Surfactants are specific functional materials that form various types of self-assemblies and affect local water ordering alongside solution properties. Such surface active agents are used extensively in gas hydrate based applications as kinetic hydrate promoters. To understand the effect of surfactant micelles on hydrate formation kinetics, a novel surfactant system capable of producing micelles at hydrate forming temperature was developed. The presence of surfactant micelles in this new system (a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…On the other end of the spectrum, the additives that are used to promote hydrate formation and find utility in one or more of the technological applications of gas hydrates, can also be divided into two clear categories: thermodynamic hydrate promoters (THPs) , and kinetic hydrate promoters (KHPs). ,, THPs (generally small hydrocarbons such as THF and DIOX) are molecules which themselves occupy cages of the formed hydrate, helping to stabilize the hydrate structure and thus shifting hydrate phase equilibrium conditions to much milder ones (lower pressures and higher temperatures), , whereas KHPs simply either shorten the hydrate nucleation period or enhance the rate of hydrate growth or both. Traditionally, the most commonly used KHPs have been surfactants such as sodium dodecyl sulfate (SDS). , …”
Section: Introductionmentioning
confidence: 99%
“…On the other end of the spectrum, the additives that are used to promote hydrate formation and find utility in one or more of the technological applications of gas hydrates, can also be divided into two clear categories: thermodynamic hydrate promoters (THPs) , and kinetic hydrate promoters (KHPs). ,, THPs (generally small hydrocarbons such as THF and DIOX) are molecules which themselves occupy cages of the formed hydrate, helping to stabilize the hydrate structure and thus shifting hydrate phase equilibrium conditions to much milder ones (lower pressures and higher temperatures), , whereas KHPs simply either shorten the hydrate nucleation period or enhance the rate of hydrate growth or both. Traditionally, the most commonly used KHPs have been surfactants such as sodium dodecyl sulfate (SDS). , …”
Section: Introductionmentioning
confidence: 99%
“…Promoters are roughly divided into two groups: kinetic and thermodynamic promoters. Thermodynamic promoters, such as tetrahydrofuran (THF), for example, enable gas hydrate formation at higher temperatures and lower pressures, as they are capable of forming hydrates on their own while stabilizing gas hydrates of other species. , Kinetic promoters, mainly surfactants, such as sodium dodecyl sulfate (SDS), accelerate gas hydrate formation. , For example, Zhong and Rogers discovered that, at SDS concentrations above the CMC, gas hydrate formation rates in quiescent systems are significantly higher than those in pure water . Recently, growing interest in amino acids has been recognized as well in this context. , Another approach to enhance hydrate formation is to take apparatus-based technical measures, for example, by using stirred, , spray, , bubble column, , or packed-bed , reactor designs, and this work focuses on the last approach.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Kinetic promoters, mainly surfactants, such as sodium dodecyl sulfate (SDS), accelerate gas hydrate formation. 28,29 For example, Zhong and Rogers discovered that, at SDS concentrations above the CMC, gas hydrate formation rates in quiescent systems are significantly higher than those in pure water. 30 Recently, growing interest in amino acids has been recognized as well in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Kalogerakis, Jamaluddin, Dholabhai, and Bishnoi proposed that surfactants reduce the nucleation barrier without altering the phase equilibria . Zhong and Rogers observed that the presence of micelles not only enhances the gas solubility but also acts as a nucleating site for faster hydrate growth. , Some studies also suggest that micelles can adsorb on solid gas hydrate surfaces and may affect the growth kinetics . However, the theory of the formation of micelles at gas hydrate formation condition is debatable due to the fact that micelles should not form below the Krafft temperature .…”
Section: Introductionmentioning
confidence: 99%